Effectiveness of Complete Systematic Land Registration (PTSL) Against Waqf Land Certification at Magelang Regency - Dakum Dakum; Nurwati Nurwati; Muhammad Irkham Firdaus (AL- IKTISAB Journal of Islamic Economic Law, 2021)
The government's policy on Complete Systematic Land Registration (PTSL) is a policy initiated by the Ministry of Agrarian Affairs of the Republic of Indonesia in 2017, then further refined in 2018 as it still has problems in its implementation. The policy is expected to expedite the existing land certification process in Indonesia, including waqf land certification. However, this policy should be tested to measure the level of effectiveness against the facilities and acceleration of the certification process, especially the waqf land certification at Magelang Regency. The purpose of this study is to analyze the effectiveness of government policies on PTSL towards accelerating the certification of waqf land at Magelang Regency. Research methods are field research and qualitative approach by checking interview results, PTSL related regulations, regulations related to registration of waqf land certification, scientific journals related to soil certification, etc. The results of this study show that the implementation of government policies on PTSL towards accelerating the certification of waqf land is not optimally implemented in Magelang Regency. This can be seen from the percentage of waqf land certification levels at Magelang Regency still low, despite experiencing a decline after the birth of government policy on PTSL.